Characteristics, properties, and functionality of fetal membranes: An overlooked area in the field of parturition - Martin, Laura [UNESP]; Richardson, Lauren; Menon, Ramkumar (Elsevier, 2018)
Throughout gestation, fetal membranes, also known as placental or amniochorion membranes, surround, and protect the fetus. Although a critical component of the intrauterine cavity, neither their cellular origin in embryo development nor their role in growth and delivery of the fetus is properly understood. The fetal membranes are comprised of cellular (amnion epithelial, amnion mesenchymal and chorion leave and trophoblast) and stromal layers (extracellular matrix made of various types of collagen) fetal origin, forming a complex and unique organ. Membranes grow and develop with the fetus and perform unique tasks independent of. This article details the origin, development, structure, function, and most importantly describe how they contribute to human parturition through a novel mechanism involving tissue aging. The novel concepts of fetal membrane aging in utero provides new insights into their potential contribution in preterm birth, a major complication of pregnancy. Additionally, we also report that fetal membranes are not an aged and dead tissue at the time of labor and delivery. The pluripotency of these cells are used in a variety of fields, forming organs in vitro and improving wound healing in clinics. This article projects the uniqueness of fetal membranes, an understudied tissue during pregnancy and parturition and its usefulness in other branches of medicine.
Keywords: Amnion epithelial cells; Amnion mesenchymal cells; Cell differentiation; Cytokines; Development; Gestation; Growth factors; Stromal cells; Wound healing